Response of human rheumatoid arthritis osteoblasts and osteoclasts to adiponectin - Krumbholz, Grit; Junker, Susann; Meier, Florian M P; Rickert, Markus; Steinmeyer, Jürgen; Rehart, Stefan; Lange, Uwe; Frommer, Klaus W; Schett, Georg; Müller-Ladner, Ulf; Neumann, Elena (Clinical and Experimental Rheumatology, 2017)
Adiponectin is an effector molecule in the pathophysiology of rheumatoid arthritis, e.g. by inducing cytokines and matrix degrading enzymes in synovial fibroblasts. There is growing evidence that adiponectin affects osteoblasts and osteoclasts although the contribution to the aberrant bone metabolism in rheumatoid arthritis is unclear. Therefore, the adiponectin effects on rheumatoid arthritis-derived osteoblasts and osteoclasts were evaluated.Adiponectin and its receptors were examined in bone tissue. Primary human osteoblasts and osteoclasts were stimulated with adiponectin and analysed using realtime polymerase chain-reaction and immunoassays. Effects on matrix-production by osteoblasts and differentiation and resorptive activity of osteoclasts were examined.Immunohistochemistry of rheumatoid arthritis bone tissue showed adiponectin expression in key cells of bone remodelling. Adiponectin altered gene expression and cytokine release in osteoblasts and increased IL-8 secretion by osteoclasts. Adiponectin inhibited osterix and induced osteoprotegerin mRNA in osteoblasts. In osteoclasts, MMP-9 and tartrate resistant acid phosphatase expression was increased. Accordingly, mineralisation capacity of osteoblasts decreased whereas resorptive activity of osteoclasts increased.The results confirm the proinflammatory potential of adiponectin and support the idea that adiponectin influences rheumatoid arthritis bone remodelling through alterations in osteoblast and osteoclast.
EVALuna2:13390